Dynamic Ultrasound Assessment of Median Nerve Mobility Changes Following Corticosteroid Injection and Carpal Tunnel Release in Patients With Carpal Tunnel Syndrome - I-Ning Lo (Frontiers in Neurology, 2021)
Decreased median nerve (MN) mobility was found in patients with carpal tunnel syndrome (CTS) and was inversely associated with symptom severity. It is unclear whether MN mobility can be restored with interventions. This study compared the changes in MN mobility and clinical outcomes after interventions. Forty-six patients with CTS received an injection (n = 23) or surgery (n = 23). Clinical outcomes [Visual Analogue Scale; Boston Carpal Tunnel Questionnaire (BCTQ), which includes the Symptom Severity Scale and Functional Status Scale; median nerve cross-sectional area; and dynamic ultrasound MN mobility parameters (amplitude, and R2 value and curvature of the fitted curves of MN transverse sliding)] were assessed at baseline and 12 weeks after the interventions. At baseline, the BCTQ-Functional Status Scale and median nerve cross-sectional area showed significant inter-treatment differences. At 12 weeks, both treatments had significant improvements in BCTQ-Symptom Severity Scale and Visual Analogue Scale scores and median nerve cross-sectional area, but with greater improvements in BCTQ-Functional Status Scale scores observed in those who received surgery than in those who received injections. MN mobility was insignificantly affected by both treatments. The additional application of dynamic ultrasound evaluation may help to discriminate the severity of CTS initially; however, its prognostic value to predict clinical outcomes after interventions in patients with CTS is limited.